2019
DOI: 10.17645/pag.v7i2.1771
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Aid Effectiveness: Revisiting the Evidence

Abstract: As research on the empirical link between aid and growth continues to grow, it is time to revisit the accumulated evidence on aid effectiveness. This paper extends previous meta-analyses, noting that the availability of more data enables us to conduct a sub-group analysis by disaggregating the sample into different time horizons and assess if there are temporal shifts in aid effectiveness. The new and updated results show that the earlier reported positive evidence of aid’s impact is robust to the inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…In particular, a large literature has considered the aggregate impact of aid on economic growth and discussed whether, on average, aid promotes, undermines, or has no effect across countries. 28 Even if aid pessimists remain sceptical about its effects, there is clear convergence in the literature about a positive impact of aid on growth, as discussed in an extensive literature (see Arndt, Jones, and Tarp 2016;Gisselquist and Tarp 2019;Jones and Tarp 2016;Mekasha and Tarp 2019;Sumner and Glennie 2015). 29 While the goal of poverty reduction can be indirectly achieved through increased growth (as discussed in section 5.1), 30 there are also potential direct impacts through programmes targeted at areas with a high number of people living below the poverty line or programmes that target lowincome households.…”
Section: Should the Focus Be On Within-or Between-country Inequality?...mentioning
confidence: 99%
“…In particular, a large literature has considered the aggregate impact of aid on economic growth and discussed whether, on average, aid promotes, undermines, or has no effect across countries. 28 Even if aid pessimists remain sceptical about its effects, there is clear convergence in the literature about a positive impact of aid on growth, as discussed in an extensive literature (see Arndt, Jones, and Tarp 2016;Gisselquist and Tarp 2019;Jones and Tarp 2016;Mekasha and Tarp 2019;Sumner and Glennie 2015). 29 While the goal of poverty reduction can be indirectly achieved through increased growth (as discussed in section 5.1), 30 there are also potential direct impacts through programmes targeted at areas with a high number of people living below the poverty line or programmes that target lowincome households.…”
Section: Should the Focus Be On Within-or Between-country Inequality?...mentioning
confidence: 99%
“…In light of the strong positive bene ts of openness to international trade, and the need for countries to simultaneously ensure a sustainable stream of public revenue in order to realize development goals, the pursuance of the TTR process should take place concurrently with measures and policies to reduce trade costs. Despite the controversy over the effectiveness of development aid in promoting economic and social development in recipient countries (e.g., Guillaumont and Wganer, 2014;Mekasha and Tarp, 2019), the present analysis has shown that such aid contributes to reducing the negative effect of trade costs on the TTR process. As a result, by scaling-up, development aid in favour of developing countries, donorcountries could help reduce trade costs, but also enhance the TTR process in developing countries.…”
Section: /38mentioning
confidence: 51%
“…After a 11 The skew reporting is likely to be due to strong preferences and interests of the authors, who are members of a research group at Copenhagen University, the DERG that is largely financed by aidmainly from the Danish aid agency Danida. Mekasha and Tarp (2019) is an update without augmenting. It neatly replicates Doucouliagos and Paldam (2015), with only a few polemic remarks.…”
Section: Discussionmentioning
confidence: 99%